Physical principles of the nuclear burning wave reactor. I - V. N. Bukanov; E. G. Vasylieva; V. L. Diemokhin; A. M. Pugach (Ядерна фізика та енергетика)
Results to support reliability of the VVER ex-vessel dosimetry neutron-activation detector spectrometric data are presented. It is shown. that detector specific activity values can be used for validation of the reactor pressure vessel radiation exposure methodology.